El Bitcoin como alternativa de inversión en los estudiantes de pregrado - Gordillo Ocampo, Ernesto Fabian (2022)
Today, one of the cryptocurrencies that has taken on great value in financial operations the Bitcoin, Because it is one of the first digital currencies to appear and also that to this day it does not present losses in its value being in the first place with respect to the rest of cryptocurrencies, hence the proper handling and control of this cryptoactive, it is efficient to strengthen and substantiate that work. Therefore, the purpose of this research is to evaluate Bitcoin as an alternative investment in undergraduate students. The research was of an exploratory, descriptive type, with a quantitative and qualitative approach, given that an evaluation of the level of knowledge of Bitcoin was made in university students, therefore, the collection of information was applied by means of surveys to 347 students stratified by career. The main findings show that 76.61% of users have minimal knowledge of Bitcoin. In addition, it was determined that 74.63% of university students do not use this cryptoactive due to the high risk of investing electronically without a regulatory entity. Another important aspect is that this business model serves as a means of investment. but as a currency exchange is not allowed